2005
DOI: 10.1242/jcs.02514
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of endothelial cells by Neisseria meningitidis requires cortactin recruitment by a phosphoinositide-3-kinase/Rac1 signalling pathway triggered by the lipo-oligosaccharide

Abstract: Type-IV-pilus-mediated adhesion of Neisseria meningitidis (also known as meningococcus) to human endothelial cells induces the formation of membrane protrusions leading to bacterial uptake. We have previously shown that these protrusions result from a Rho- and Cdc42-dependent cortical actin polymerization, and from the activation of the ErbB2 tyrosine-kinase receptor and the Src kinase, leading to tyrosine phosphorylation of cortactin. We report here that N. meningitidis mutants expressing a deglycosylated lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 47 publications
0
81
1
Order By: Relevance
“…For our study, we chose N. meningitidis MC58 as a prototype ST-32 cc strain and strain ␣711 as a genetically related carrier isolate from the ST-32 cc. We also included N. meningitidis isolate 8013/clone 12 from the ST-18 cc (also known as clone 12 or 2C43), which has been used to study the interaction between N. meningitidis and brain endothelial cells (57)(58)(59)(60). Isolate ␣4 was chosen as a genetically related carrier isolate to 8013/clone 12.…”
Section: Discussionmentioning
confidence: 99%
“…For our study, we chose N. meningitidis MC58 as a prototype ST-32 cc strain and strain ␣711 as a genetically related carrier isolate from the ST-32 cc. We also included N. meningitidis isolate 8013/clone 12 from the ST-18 cc (also known as clone 12 or 2C43), which has been used to study the interaction between N. meningitidis and brain endothelial cells (57)(58)(59)(60). Isolate ␣4 was chosen as a genetically related carrier isolate to 8013/clone 12.…”
Section: Discussionmentioning
confidence: 99%
“…The only study of loss of cortactin function in an intact organism is in Drosophila, where complete loss-of-function mutations of the sole cortactin gene had only minor effects, producing smaller F-actin ring canals of germline cells and impaired migration of border cells in oogenesis (Somogyi and Rorth, 2004). In cultured cells, a variety of studies point to a role for cortactin in actin-based processes such as pathogen invasion (Lambotin et al, 2005;Selbach and Backert, 2005), endocytosis (Merrifield et al, 2005;Sauvonnet et al, 2005), post-Golgi transport (Cao et al, 2005), cell adhesion (El Sayegh et al, 2004;Helwani et al, 2004), and lamellipodial persistence (Bryce et al, 2005). In these studies, cortactin was generally found to associate with sites of actin assembly, and, in some cases, expression of cortactin mutants or knockdown of cortactin produced partial loss of actin-based motility or actin cytoskeleton assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical actin is then polymerized in a Rho GTPase-and Cdc42-dependent manner, which leads to the formation of cell membrane protrusions (186). In human bone marrow endothelial cells, the recruitment of cortactin and formation of membrane protrusions were also shown to be dependent on the activation of a phosphoinositide-3-kinase/Rac1 signaling pathway by lipooligosaccharide (190).…”
Section: Bacterial Mechanisms Of Brain Invasionmentioning
confidence: 98%